Screening of wheat grains enriched with wall-bound phenolic compounds - Yi-Lin Gong; Jin-Ying Gou (MethodsX, 2023)
Phenolic compounds are dominant antioxidant factors in whole grains and are essential quality traits in future breeding programs. We proposed a robust set of methods for extraction, screening, and quantitative analysis of soluble and wall-bound (WB) phenolic compounds from fine powder and fine powder products using a 96 Wells UV Flat Bottom and subsequent UHPLC-DAD validation of candidate samples. The plate-UHPLC strategy significantly simplifies the screening of phenolic-enriched grains, reduces the screening cost, saves harmful organic chemicals, and contributes to developing novel health-promoting varieties.